Preparation method of lithium ion sieve membrane material with temperature-sensitive intelligent regulation and control function
By combining the temperature-sensitive material with the lithium-ion sieve material, lithium-ion sieve membrane material with temperature-sensitive intelligent regulation functions is prepared, which solves the shortcomings of traditional materials in lithium-ion extraction and recovery efficiency, selectivity and stability, and achieves efficient selective separation of lithium ions and improves the adaptability and stability of materials.
Patent Information
- Application Number
- CN202510210820.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-04-29
AI Technical Summary
Traditional lithium-ion sieve membrane materials have shortcomings in lithium ion extraction and recovery efficiency, selectivity and stability, especially in different temperature environments, which lacks intelligent regulation capabilities and is difficult to meet practical application needs.
Combining the temperature-sensitive material with the lithium ion sieve material, by preparing the lithium ion sieve membrane material with the temperature-sensitive intelligent regulation function, using thermosensitive polymer materials such as N-isopropyl acrylamide and acrylamide to build a dual interpenetrating cross-linking network to achieve the temperature responsiveness of the material, thereby regulating the pore size and surface charge.
It realizes efficient selective separation of lithium ions, improves the extraction and recovery efficiency of lithium ions, enhances the adaptability and stability of materials, and provides a new solution for the sustainable development of lithium ion battery technology.
Smart Images

Figure CN119899311A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a lithium ion sieve membrane material. Background Art
[0002] Lithium-ion batteries have shown wide application potential in many fields such as electric vehicles and portable electronic devices due to their advantages such as high energy density and long cycle life. However, the scarcity of lithium resources and the uneven geographical distribution highlight the importance of improving the efficiency of lithium ion extraction and recovery, and have become an important topic. At present, the adsorption method is considered to be the most promising method for extracting lithium due to its good selectivity, high extraction rate and easy continuous operation. Lithium ion sieve is a highly efficient selective adsorbent with high chemical stability, strong lithium adsorption capacity and unique chemical structure. Traditional lithium ion sieve membrane materials have limitations in selectivity, stability and performance regulation, and are difficult to meet the needs of practical applications. In particular, traditional materials lack intelligent regulation capabilities for changes in lithium ion separation efficiency under different temperature environments. Therefore, it is of great significance to develop a lithium ion sieve membrane material with intelligent regulation functions.
[0003] Thermosensitive materials are a type of functional material that can respond to external temperature changes. Their physical and chemical properties (such as hydrophilicity, hydrophobicity, swelling, etc.) will change significantly with temperature changes, providing a new idea for the development of intelligent lithium ion sieving membrane materials. The present invention innovatively combines thermosensitive materials with lithium ion sieving materials to develop intelligent lithium ion sieving membrane materials with temperature responsiveness, thereby realizing intelligent regulation of lithium ion separation efficiency. Summary of the invention
[0004] The purpose of the present invention is to solve the problems that the lithium ion sieve membrane materials prepared by the existing methods have low extraction and recovery efficiency of lithium ions, poor selectivity and stability, inability to respond to temperature and cannot meet the needs of practical applications, and to provide a method for preparing a lithium ion sieve membrane material with temperature-sensitive intelligent control function.
[0005] The present invention provides a method for preparing a lithium ion sieve membrane material with a temperature-sensitive intelligent control function, which can intelligently control its pore size and surface charge according to temperature, thereby achieving efficient and selective separation of lithium ions. Compared with the prior art, the lithium ion sieve membrane material with a temperature-sensitive intelligent control function prepared by the present invention not only improves the extraction and recovery efficiency of lithium ions, but also enhances the adaptability and stability of the material, providing a new solution for the sustainable development of lithium ion battery technology.
[0006] A method for preparing a lithium ion sieve membrane material with a temperature-sensitive intelligent control function is specifically completed by the following steps:
[0007] 1. Preparation of manganese oxide lithium ion sieve:
[0008] ①, dissolve KMnO4 in ethanol solution, transfer to a high-pressure reactor, perform hydrothermal reaction at 140℃~160℃, cool to room temperature naturally after the reaction, filter, wash the obtained solid matter with water until neutral, and then vacuum dry to obtain γ-MnOOH;
[0009] ②, mix the γ-MnOOH and LiOH solutions evenly, transfer them to a high-pressure reactor, and perform hydrothermal reaction at 120℃~130℃ for a period of time. After the reaction is completed, naturally cool to room temperature, filter, wash the solid matter, and dry to obtain the reaction product;
[0010] ③. Transfer the reaction product to a muffle furnace and calcine it at 400℃~450℃ for a period of time to obtain the ion sieve precursor Li 1.6 Mn 1.6 O4 material; using dilute hydrochloric acid to ion sieve precursor Li 1.6 Mn 1.6 The O4 material is subjected to acid leaching treatment, then filtered, the obtained solid matter is washed with water until neutral, and then vacuum dried to obtain a manganese oxide lithium ion sieve;
[0011] 2. Preparation of temperature-sensitive polymer composite solution:
[0012] Dissolve N-isopropylacrylamide and acrylamide in deionized water, stir magnetically at room temperature until the solution is clear, add manganese oxide lithium ion sieve, sonicate for a period of time, add N,N'-methylenebisacrylamide, stir for a period of time, and obtain a temperature-sensitive polymer material composite solution;
[0013] 3. Preparation of lithium ion sieve membrane materials with temperature-sensitive intelligent control function:
[0014] A temperature-sensitive polymer material composite solution is cast on a clean glass plate and a porous membrane is prepared by a phase inversion method; the obtained porous membrane is heat-treated to obtain a lithium ion sieve membrane material with temperature-sensitive intelligent control function.
[0015] The principle of the present invention is:
[0016] 1. The thermosensitive polymer material (N-isopropylacrylamide, NIPAM) in the present invention has a specific critical solution temperature (LCST); when the temperature is lower than the LCST, the polymer chain is hydrophilic, and the lithium ion sieve membrane material (TSHM) with temperature-sensitive intelligent regulation function is in a swollen state, and the porosity of the membrane increases, which is conducive to the rapid transmission and diffusion of lithium ions; when the temperature is higher than the LCST, the polymer chain becomes hydrophobic, causing the TSHM membrane material to shrink, reducing the porosity of the membrane, and limiting or preventing the passage of lithium ions;
[0017] Second, the present invention uses N-isopropylacrylamide (NIPAM) as a thermosensitive polymer, and uses acrylamide as an auxiliary to construct a double interpenetrating cross-linked network, which can adjust and optimize the temperature-sensitive range, so that the material can be intelligently controlled within a wider temperature range; at the same time, the copolymerization of the two monomers forms a network structure with higher porosity, providing more adsorption sites, thereby increasing the adsorption capacity for lithium ions;
[0018] 3. The change of temperature in the present invention can affect the activity of ion exchange groups, and then affect the charge density on the surface of the material; heating may increase the movement of polymer chains, making it easier for ion exchange groups to bind to or release lithium ions, thereby regulating the charge state of the membrane surface.
[0019] The present invention provides a method for preparing a lithium ion sieve membrane material with a temperature-sensitive intelligent control function, and its beneficial effects are embodied in:
[0020] 1. It can intelligently regulate its pore size and surface charge according to environmental conditions, thereby achieving efficient and selective separation of lithium ions and solving the limitations of selective regulation;
[0021] Second, N-isopropylacrylamide is used as a thermosensitive polymer and acrylamide is used as an auxiliary to construct a double interpenetrating cross-linked network, which solves the problem that the existing lithium ion sieve membrane materials cannot effectively regulate lithium ion transmission in a wide temperature range;
[0022] 3. By introducing thermosensitive polymers, the membrane material has a rich porous network structure, showing a higher lithium ion adsorption capacity and improving the performance of the overall material;
[0023] 4. The intelligent control characteristics of material design simplify the adsorption operation process, help improve its stability in multiple adsorption-desorption cycles, and extend its service life;
[0024] 5. The adsorption capacity of the lithium ion sieve membrane material with temperature-sensitive intelligent regulation function prepared by the present invention is 18.5 mg / g, and the selectivity is Li + >Mg 2+ >Ca 2+ >Na + >K + . BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a scanning electron microscope image of the lithium ion sieve membrane material with temperature-sensitive intelligent control function prepared in Example 1;
[0026] Figure 2 The adsorption capacity change diagram and temperature response efficiency diagram of the lithium ion sieve membrane material with temperature-sensitive intelligent regulation function prepared at different ion sieve HMO dosages in Examples 1, 2 and 3;
[0027] Figure 3 The adsorption capacity diagram and temperature response efficiency diagram of the lithium ion sieve membrane material with temperature-sensitive intelligent regulation function prepared in Examples 1, 4 and 5 at different cross-linking agent dosages;
[0028] Figure 4 The adsorption capacity diagram and temperature response efficiency diagram of lithium ion sieve membrane materials with temperature-sensitive intelligent regulation function prepared in different ratios of NIPAM to PAM in Examples 1, 6 and 7. DETAILED DESCRIPTION
[0029] Specific implementation method 1: This implementation method is a method for preparing a lithium ion sieve membrane material with a temperature-sensitive intelligent control function, which is specifically completed according to the following steps:
[0030] 1. Preparation of manganese oxide lithium ion sieve:
[0031] ①, dissolve KMnO4 in ethanol solution, transfer to a high-pressure reactor, perform hydrothermal reaction at 140℃~160℃, cool to room temperature naturally after the reaction, filter, wash the obtained solid matter with water until neutral, and then vacuum dry to obtain γ-MnOOH;
[0032] ②, mix the γ-MnOOH and LiOH solutions evenly, transfer them to a high-pressure reactor, and perform hydrothermal reaction at 120℃~130℃ for a period of time. After the reaction is completed, naturally cool to room temperature, filter, wash the solid matter, and dry to obtain the reaction product;
[0033] ③. Transfer the reaction product to a muffle furnace and calcine it at 400℃~450℃ for a period of time to obtain the ion sieve precursor Li 1.6 Mn 1.6 O4 material; using dilute hydrochloric acid to ion sieve precursor Li 1.6 Mn 1.6 The O4 material is subjected to acid leaching treatment, then filtered, the obtained solid matter is washed with water until neutral, and then vacuum dried to obtain a manganese oxide lithium ion sieve;
[0034] 2. Preparation of temperature-sensitive polymer composite solution:
[0035] Dissolve N-isopropylacrylamide and acrylamide in deionized water, stir magnetically at room temperature until the solution is clear, add manganese oxide lithium ion sieve, sonicate for a period of time, add N,N'-methylenebisacrylamide, stir for a period of time, and obtain a temperature-sensitive polymer material composite solution;
[0036] 3. Preparation of lithium ion sieve membrane materials with temperature-sensitive intelligent control function:
[0037] A temperature-sensitive polymer material composite solution is cast on a clean glass plate and a porous membrane is prepared by a phase inversion method; the obtained porous membrane is heat-treated to obtain a lithium ion sieve membrane material with temperature-sensitive intelligent control function.
[0038] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that: the mass ratio of KMnO4 to ethanol solution described in step 1① is (0.9g-1.2g):(30mL-40mL); the mass fraction of ethanol solution described in step 1① is 2.5%-3%. The other steps are the same as those in specific implementation method 1.
[0039] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that: the time of the hydrothermal reaction in step 1① is 10h to 12h; the temperature of the vacuum drying in step 1① is 60℃ to 70℃, and the time of the vacuum drying is 4h to 6h. The other steps are the same as those in specific implementation method 1 or 2.
[0040] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: the mass ratio of γ-MnOOH described in step 1 ② to the volume ratio of LiOH solution is (2g to 3g): (11.5mL to 17.3mL); the concentration of LiOH solution described in step 1 ② is 3mol / L to 4mol / L. The other steps are the same as those of specific embodiments 1 to 3.
[0041] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: the hydrothermal reaction time in step 1 ② is 20h to 24h; in step 1 ②, the solid material is washed 3 to 5 times with deionized water, and then dried at 60°C to 70°C for 4h to 6h. The other steps are the same as those in specific embodiments 1 to 4.
[0042] Specific embodiment 6: The difference between this embodiment and specific embodiments 1 to 5 is that the calcination time in step 1 ③ is 5h to 7h; the concentration of dilute hydrochloric acid in step 1 ③ is 0.1 mol / L; dilute hydrochloric acid is used in step 1 ③ to calcine the ion sieve precursor Li 1.6 Mn 1.6 The O4 material is subjected to acid leaching for 10 to 12 hours; the vacuum drying temperature in step 1③ is 60 to 70°C, and the vacuum drying time is 4 to 6 hours. The other steps are the same as those in specific embodiments 1 to 5.
[0043] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: the mass ratio of N-isopropylacrylamide and acrylamide described in step 2 is (0.2-0.6):(0.2-0.6); the mass ratio of N-isopropylacrylamide and manganese oxide lithium ion sieve described in step 2 is (0.2-0.6):(0.1-0.3). The other steps are the same as specific embodiments 1 to 6.
[0044] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that: the mass ratio of N-isopropylacrylamide and N,N'-methylenebisacrylamide described in step 2 is (0.2-0.6):(0.03-0.07); the mass ratio of N-isopropylacrylamide described in step 2 to deionized water is (0.2g-0.6g):(3mL-5mL). The other steps are the same as specific embodiments 1 to 7.
[0045] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that the ultrasonic time in step 2 is 10 to 20 minutes, and the stirring time in step 2 is 20 to 40 minutes. The other steps are the same as those in specific embodiments 1 to 8.
[0046] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that: the phase inversion method described in step 3 is to immerse the glass plate containing the temperature-sensitive polymer material composite solution in deionized water at a temperature of 25°C to 30°C for 10min to 20min to obtain a porous membrane; the heat treatment temperature described in step 3 is 80°C to 90°C, and the heat treatment time is 1h to 3h. The other steps are the same as those of specific embodiments 1 to 9.
[0047] The following examples are used to verify the beneficial effects of the present invention:
[0048] The amount of HMO used was varied in Examples 1 to 3 to determine the best effect.
[0049] Example 1: A method for preparing a lithium ion sieve membrane material with temperature-sensitive intelligent control function is specifically completed by the following steps:
[0050] 1. Preparation of manganese oxide lithium ion sieve:
[0051] ①, dissolve KMnO4 in ethanol solution with a mass fraction of 2.5%, then transfer to a high-pressure reactor, perform hydrothermal reaction at a temperature of 150°C for 12 hours, naturally cool to room temperature after the reaction, filter, wash the obtained solid matter with water until it is neutral, and then vacuum dry at 60°C for 5 hours to obtain γ-MnOOH;
[0052] The volume ratio of the mass of KMnO4 described in step 1① to the ethanol solution with a mass fraction of 2.5% is 1.05g:36mL;
[0053] ②, mix the γ-MnOOH and LiOH solutions evenly, transfer them to a high-pressure reactor, and perform a hydrothermal reaction at 120°C for 24 hours. After the reaction is completed, cool them naturally to room temperature, filter them, wash the solid matter, and dry them to obtain a reaction product;
[0054] The mass ratio of γ-MnOOH described in step 1② to the volume ratio of LiOH solution is 2g:15mL;
[0055] The concentration of the LiOH solution described in step 1② is 4 mol / L;
[0056] In step 1②, the solid material is washed 5 times with deionized water and then dried at 60°C for 5 hours;
[0057] ③. Transfer the reaction product to a muffle furnace and calcine at 400 °C for 6 h to obtain the ion sieve precursor Li 1.6 Mn 1.6 O4 material; using dilute hydrochloric acid to ion sieve precursor Li 1.6 Mn 1.6 The O4 material is subjected to acid leaching, then filtered, the obtained solid matter is washed with water until neutral, and then vacuum dried to obtain manganese oxide lithium ion sieve (HMO);
[0058] The concentration of the dilute hydrochloric acid described in step 1③ is 0.1 mol / L;
[0059] In step 1③, dilute hydrochloric acid is used to treat the ion sieve precursor Li 1.6 Mn 1.6 O4 material was acid leached for 12h;
[0060] The vacuum drying temperature in step 1 (3) is 60°C and the vacuum drying time is 5h;
[0061] 2. Preparation of temperature-sensitive polymer composite solution:
[0062] 0.5 g of N-isopropylacrylamide (NIPAM) and 0.5 g of acrylamide (AM) were dissolved in 3 mL of deionized water, and magnetically stirred at room temperature until the solution was clear, and then 0.2 g of manganese oxide lithium ion sieve (HMO) was added, and ultrasonicated for 10 min, and then 0.05 g of N,N'-methylenebisacrylamide was added, and stirred for 30 min to obtain a temperature-sensitive polymer material composite solution;
[0063] 3. Preparation of lithium ion sieve membrane materials with temperature-sensitive intelligent control function:
[0064] The thermosensitive polymer material composite solution was cast on a clean glass plate, the film was scraped to a thickness of 200 μm, and then immediately immersed in deionized water at 25°C for 10 min; the obtained porous membrane was heat treated at 80°C for 1 h to obtain a lithium ion sieve membrane material (TSHM) with temperature-sensitive intelligent control function.
[0065] The lithium ion adsorption capacity of the lithium ion sieving membrane material (TSHM) with temperature-sensitive intelligent regulation function prepared in Example 1 reaches 18.5 mg / g, and the temperature response regulation efficiency is 92%.
[0066] Example 2: The difference between this example and Example 1 is that in step 2, 0.5 g of N-isopropylacrylamide and 0.5 g of acrylamide are dissolved in 3 mL of deionized water, magnetically stirred at room temperature until the solution is clear, and then 0.1 g of manganese oxide lithium ion sieve (HMO) is added, ultrasonicated for 10 min, and then 0.05 g of N, N'-methylenebisacrylamide is added, stirred for 30 min, to obtain a temperature-sensitive polymer material composite solution. The other steps and parameters are the same as those in Example 1.
[0067] Compared with Example 1, HMO is used as an active site for lithium ion adsorption, and the reduced amount leads to a decrease in adsorption capacity. The lithium ion adsorption capacity of the lithium ion sieving membrane material (TSHM) with temperature-sensitive intelligent regulation function prepared in Example 2 reaches 15.2 mg / g, and the temperature response regulation efficiency is 85%, which is slightly lower than that in Example 1.
[0068] Example 3: The difference between this example and Example 1 is that in step 2, 0.5 g of N-isopropylacrylamide and 0.5 g of acrylamide are dissolved in 3 mL of deionized water, magnetically stirred at room temperature until the solution is clear, and then 0.3 g of manganese oxide lithium ion sieve (HMO) is added, ultrasonicated for 10 min, and then 0.05 g of N, N'-methylenebisacrylamide is added, stirred for 30 min, to obtain a temperature-sensitive polymer material composite solution. The other steps and parameters are the same as those in Example 1.
[0069] Compared with Example 1, the excess HMO (such as 0.3 g) causes uneven dispersion of the composite material and covers some active sites, affecting the structural stability and adsorption performance of the membrane. The lithium ion sieve membrane material (TSHM) with temperature-sensitive intelligent regulation function prepared in Example 3 has a lithium ion adsorption capacity of 16.7 mg / g and a temperature response regulation efficiency of 88%, which is lower than that in Example 1.
[0070] The amount of crosslinking agent used was varied in Examples 4 and 5 to determine the best effect.
[0071] Example 4: The difference between this example and Example 1 is that in step 2, 0.5 g of N-isopropylacrylamide and 0.5 g of acrylamide are dissolved in 3 mL of deionized water, magnetically stirred at room temperature until the solution is clear, and then 0.2 g of manganese oxide lithium ion sieve (HMO) is added, ultrasonicated for 10 min, and then 0.03 g of N, N'-methylenebisacrylamide is added, stirred for 30 min, to obtain a temperature-sensitive polymer material composite solution. The other steps and parameters are the same as those in Example 1.
[0072] Compared with Example 1, the lithium ion adsorption capacity of the lithium ion sieve membrane material (TSHM) with temperature-sensitive intelligent regulation function prepared in Example 4 reaches 17.8 mg / g, and the temperature response regulation efficiency is 90%, which is slightly lower than that in Example 1.
[0073] Example 5: The difference between this example and Example 1 is that in step 2, 0.5 g of N-isopropylacrylamide and 0.5 g of acrylamide are dissolved in 3 mL of deionized water, magnetically stirred at room temperature until the solution is clear, and then 0.2 g of manganese oxide lithium ion sieve (HMO) is added, ultrasonicated for 10 min, and then 0.07 g of N, N'-methylenebisacrylamide is added, stirred for 30 min, to obtain a temperature-sensitive polymer material composite solution. The other steps and parameters are the same as those in Example 1.
[0074] Compared with Example 1, the excess cross-linking agent (0.07 g) leads to the closure of membrane pores, restricting the diffusion of lithium ions. The movement of the temperature-sensitive segments is inhibited, the adsorption capacity and the regulation efficiency are reduced. The lithium ion adsorption capacity of the lithium ion sieve membrane material (TSHM) with temperature-sensitive intelligent regulation function prepared in Example 5 reaches 14.3 mg / g, and the temperature response regulation efficiency is 82%, which is lower than that in Example 1.
[0075] The ratio of NIPAM to acrylamide was varied in Examples 6 and 7 to determine the best effect.
[0076] Example 6: The difference between this example and Example 1 is that in step 2, 0.6 g of N-isopropylacrylamide and 0.2 g of acrylamide are dissolved in 3 mL of deionized water, magnetically stirred at room temperature until the solution is clear, and then 0.2 g of manganese oxide lithium ion sieve (HMO) is added, ultrasonicated for 10 min, and then 0.05 g of N, N'-methylenebisacrylamide is added, stirred for 30 min, to obtain a temperature-sensitive polymer material composite solution. The other steps and parameters are the same as those in Example 1.
[0077] Compared with Example 1, the reduction of acrylamide leads to a decrease in hydrophilicity and a decrease in adsorption capacity. The lithium ion adsorption capacity of the lithium ion sieve membrane material (TSHM) with temperature-sensitive intelligent regulation function prepared in Example 6 reaches 14.5 mg / g, and the temperature response regulation efficiency is 78%, which is lower than that in Example 1.
[0078] Example 7: The difference between this example and Example 1 is that in step 2, 0.2 g of N-isopropylacrylamide and 0.6 g of acrylamide are dissolved in 3 mL of deionized water, magnetically stirred at room temperature until the solution is clear, and then 0.2 g of manganese oxide lithium ion sieve (HMO) is added, ultrasonicated for 10 min, and then 0.05 g of N,N'-methylenebisacrylamide is added, stirred for 30 min, to obtain a temperature-sensitive polymer material composite solution. The other steps and parameters are the same as those in Example 1.
[0079] Compared with Example 1, the excessive acrylamide (1:3) resulted in excessive hydrophilicity, significantly reduced temperature sensitivity, and significantly reduced adsorption capacity. The lithium ion adsorption capacity of the lithium ion sieve membrane material (TSHM) with temperature-sensitive intelligent regulation function prepared in Example 6 reached 12.1 mg / g, and the temperature response regulation efficiency was 65%, which was lower than that in Example 1.
[0080] Figure 1 This is a scanning electron microscope image of the lithium ion sieve membrane material with temperature-sensitive intelligent control function prepared in Example 1;
[0081] from Figure 1 It can be seen that the prepared lithium ion sieve membrane material (TSHM) with temperature-sensitive intelligent regulation function shows a rich porous network structure. Due to the copolymerization of ion sieve and temperature-sensitive polymer monomer, the ion sieve membrane material (TSHM) forms a high-porosity network structure and uniform channels, providing more active sites to improve the adsorption capacity of the ion sieve membrane.
[0082] Figure 2 The adsorption capacity change diagram and temperature response efficiency diagram of the lithium ion sieve membrane material with temperature-sensitive intelligent regulation function prepared at different ion sieve HMO dosages in Examples 1, 2 and 3;
[0083] Figure 2 The horizontal axis 0.2 represents Example 1, 0.1 represents Example 2, and 0.3 represents Example 3;
[0084] Figure 2 The right figure in the figure is the temperature response efficiency diagram, which is obtained by measuring the adsorption amount at 25℃ and 40℃ with different ion sieve HMO dosages and calculating the change rate.
[0085] from Figure 2It can be seen that in order to explore the effect of HMO dosage on adsorption capacity and temperature response regulation efficiency, the dosage of ion sieve HMO was changed. When HMO was 0.1g, the dosage was reduced, the active sites for lithium ion adsorption were reduced, and the swelling-contraction behavior of the thermosensitive polymer chain was restricted, resulting in a decrease in adsorption capacity, the lithium ion adsorption amount was 15.2mg / g, and the temperature response regulation efficiency was 85%; when HMO was 0.3g, excessive HMO caused some active sites to be covered, affecting the adsorption performance of the membrane, the lithium ion adsorption amount was 16.7mg / g, and the temperature response regulation efficiency was 88%; Overall, when the HMO dosage was 0.2g, the adsorption amount and temperature response efficiency reached the optimal balance.
[0086] Figure 3 The adsorption capacity diagram and temperature response efficiency diagram of the lithium ion sieve membrane material with temperature-sensitive intelligent regulation function prepared in Examples 1, 4 and 5 at different cross-linking agent dosages;
[0087] Figure 3 The middle abscissa 0.05 represents Example 1, 0.03 represents Example 4, and 0.07 represents Example 5;
[0088] Figure 3 The right figure in the figure is the temperature response efficiency diagram, which is obtained by measuring the adsorption amount at 25℃ and 40℃ with different cross-linking agent dosages and calculating the change rate.
[0089] from Figure 3 It can be seen that in order to explore the effect of different cross-linking agents on the adsorption amount and temperature response regulation efficiency, when the amount of cross-linking agent is 0.03g, the cross-linking density is insufficient, resulting in a loose membrane structure, the adsorption amount is 17.8mg / g, and the temperature response regulation efficiency is 90%; when the amount of cross-linking agent is 0.07g, excessive cross-linking leads to dense membrane pores, which limits ion diffusion, the adsorption amount is 14.3mg / g, and the temperature response regulation efficiency is 82%; On the whole, when the amount of cross-linking agent is 0.05g, the adsorption amount and temperature response efficiency reach the best balance.
[0090] Figure 4 The adsorption capacity diagram and temperature response efficiency diagram of lithium ion sieve membrane materials with temperature-sensitive intelligent regulation function prepared in different ratios of NIPAM to AM in Examples 1, 6 and 7;
[0091] Figure 4 1:1 represents Example 1, 3:1 represents Example 6, and 1:3 represents Example 7;
[0092] Figure 4 The right figure in the figure is the temperature response efficiency diagram, which is obtained by measuring the adsorption amount at 25℃ and 40℃ at different ratios of NIPAM to AM and calculating the change rate.
[0093] from Figure 4It can be seen that in order to explore the effect of different ratios of NIPAM and AM on the adsorption amount and temperature response regulation efficiency, when NIPAM:AM is 3:1, the reduction of acrylamide leads to a decrease in hydrophilicity and adsorption capacity, the adsorption amount is 14.5mg / g, and the temperature response regulation efficiency is 78%; when NIPAM:AM is 1:3, excessive acrylamide leads to excessive hydrophilicity, a significant decrease in temperature sensitivity, and a significant decrease in adsorption capacity. The adsorption amount is 12.1mg / g, and the temperature response regulation efficiency is 65%; Overall, when NIPAM:AM is 1:1, the adsorption amount and temperature response efficiency reach the best balance.
Claims
1. A method for preparing a lithium ion sieve membrane material with temperature-sensitive intelligent control function, characterized in that The preparation method is specifically completed according to the following steps:
1. Preparation of manganese oxide lithium ion sieve: ①, dissolve KMnO4 in ethanol solution, transfer to a high-pressure reactor, perform hydrothermal reaction at 140℃~160℃, cool to room temperature naturally after the reaction, filter, wash the obtained solid matter with water until neutral, and then vacuum dry to obtain γ-MnOOH; ②, mix the γ-MnOOH and LiOH solutions evenly, transfer them to a high-pressure reactor, and perform hydrothermal reaction at 120℃~130℃ for a period of time. After the reaction is completed, naturally cool to room temperature, filter, wash the solid matter, and dry to obtain the reaction product; ③. Transfer the reaction product to a muffle furnace and calcine it at 400℃~450℃ for a period of time to obtain the ion sieve precursor Li 1.6 Mn 1.6 O4 material; using dilute hydrochloric acid to ion sieve precursor Li 1.6 Mn 1.6 The O4 material is subjected to acid leaching treatment, then filtered, the obtained solid matter is washed with water until neutral, and then vacuum dried to obtain a manganese oxide lithium ion sieve; 2. Preparation of temperature-sensitive polymer composite solution: Dissolve N-isopropylacrylamide and acrylamide in deionized water, stir magnetically at room temperature until the solution is clear, add manganese oxide lithium ion sieve, sonicate for a period of time, add N,N'-methylenebisacrylamide, stir for a period of time, and obtain a temperature-sensitive polymer material composite solution; 3. Preparation of lithium ion sieve membrane materials with temperature-sensitive intelligent control function: A temperature-sensitive polymer material composite solution is cast on a clean glass plate and a porous membrane is prepared by a phase inversion method; the obtained porous membrane is heat-treated to obtain a lithium ion sieve membrane material with temperature-sensitive intelligent control function.
2. The method for preparing a lithium ion sieve membrane material with temperature-sensitive intelligent control function according to claim 1, characterized in that The mass ratio of KMnO4 described in step 1① to the volume ratio of the ethanol solution is (0.9g~1.2g):(30mL~40mL); the mass fraction of the ethanol solution described in step 1① is 2.5%~3%.
3. The method for preparing a lithium ion sieve membrane material with temperature-sensitive intelligent control function according to claim 1, characterized in that The time of the hydrothermal reaction described in step 1① is 10h to 12h; the temperature of the vacuum drying described in step 1① is 60℃ to 70℃, and the time of the vacuum drying is 4h to 6h.
4. The method for preparing a lithium ion sieve membrane material with temperature-sensitive intelligent control function according to claim 1, characterized in that The volume ratio of the mass of γ-MnOOH described in step 1② to the LiOH solution is (2g~3g):(11.5mL~17.3mL); the concentration of the LiOH solution described in step 1② is 3mol / L~4mol / L.
5. The method for preparing a lithium ion sieve membrane material with temperature-sensitive intelligent control function according to claim 1, characterized in that The time of the hydrothermal reaction in step 1 ② is 20h to 24h; in step 1 ②, the solid material is washed 3 to 5 times with deionized water, and then dried at 60°C to 70°C for 4h to 6h.
6. The method for preparing a lithium ion sieve membrane material with temperature-sensitive intelligent control function according to claim 1, characterized in that The calcination time in step 1 ③ is 5h to 7h; the concentration of dilute hydrochloric acid in step 1 ③ is 0.1 mol / L; dilute hydrochloric acid is used in step 1 ③ to calcine the ion sieve precursor Li 1.6 Mn 1.6 The O4 material is subjected to acid leaching for 10 h to 12 h; the vacuum drying temperature described in step 1③ is 60°C to 70°C, and the vacuum drying time is 4 h to 6 h.
7. The method for preparing a lithium ion sieve membrane material with temperature-sensitive intelligent control function according to claim 1, characterized in that The mass ratio of N-isopropylacrylamide and acrylamide described in step 2 is (0.2-0.6):(0.2-0.6); the mass ratio of N-isopropylacrylamide and manganese oxide lithium ion sieve described in step 2 is (0.2-0.6):(0.1-0.3).
8. The method for preparing a lithium ion sieve membrane material with temperature-sensitive intelligent control function according to claim 1, characterized in that The mass ratio of N-isopropylacrylamide and N,N'-methylenebisacrylamide described in step 2 is (0.2-0.6):(0.03-0.07); the volume ratio of the mass of N-isopropylacrylamide described in step 2 to deionized water is (0.2g-0.6g):(3mL-5mL).
9. The method for preparing a lithium ion sieve membrane material with temperature-sensitive intelligent control function according to claim 1, characterized in that The ultrasonic time in step 2 is 10 min to 20 min; the stirring time in step 2 is 20 min to 40 min.
10. The method for preparing a lithium ion sieve membrane material with temperature-sensitive intelligent control function according to claim 1, characterized in that The phase inversion method described in step three is to immerse the glass plate containing the temperature-sensitive polymer material composite solution in deionized water at a temperature of 25°C to 30°C for 10min to 20min to obtain a porous membrane; the heat treatment temperature described in step three is 80°C to 90°C, and the heat treatment time is 1h to 3h.
Citation Information
Patent Citations
Preparation method of temperature-sensitive macroporous acrylamide / N-isopropyl acrylamide composite microsphere
CN102408515A
Preparation method and application of lithium-manganese type ionic sieve composite membrane
CN106621854A
Temperature-sensitive ion-imprinted adsorption material based on polysaccharide, preparation method and application of adsorption material
CN109967050A
Preparation of conductive manganese-titanium lithium ion sieve / graphene composite hydrogel and application of conductive manganese-titanium lithium ion sieve / graphene composite hydrogel in extraction of lithium from salt lake brine
CN111250063A
Preparation method and application of uranium / lithium synchronous adsorption material
CN113559829A